2014
DOI: 10.1111/wvn.12027
|View full text |Cite
|
Sign up to set email alerts
|

Sugar or High Fructose Corn Syrup—What Should Nurses Teach Patients and Families?

Abstract: The evidence suggests that fructose, found in both table sugar and HFCS, has a negative effect on health outcomes. Clinicians should teach patients and families that all sugar consumption should be closely monitored and kept below the 40 g/day recommended by the World Health Organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The form of fructose commonly used by industry for these beverages is HFCS. This type of sugar has been shown to have detrimental effects on health [Sobel and Dalby, 2014; Chan et al, 2014]. Recent in vitro studies have shown that HFCS has a higher acidogenic potential than sucrose [Ma et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…The form of fructose commonly used by industry for these beverages is HFCS. This type of sugar has been shown to have detrimental effects on health [Sobel and Dalby, 2014; Chan et al, 2014]. Recent in vitro studies have shown that HFCS has a higher acidogenic potential than sucrose [Ma et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…HFCS is a fructose-glucose liquid sweetener alternative to sucrose first introduced to the food and beverage industry in the 1970s, and containing 42% to 55% fructose and glucose, depending on the application (7,8). There are many reports about the different physiological effects of fructose and glucose.…”
mentioning
confidence: 99%